The Burden of Indirect Causes of Maternal Morbidity and Mortality in the Process of Obstetric Transition: A Cross-Sectional Multicenter Study - Cirelli, Jessica Fernandes; Surita, Fernanda Garanhani; Costa, Maria Laura; Parpinelli, Mary Angela; Haddad, Samira Maerrawi; Cecatti, José Guilherme (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2018)
Objective The aim of this study is to evaluate the burden of indirect causes of maternal morbidity/mortality in Brazil.Methods Secondary analysis of a multicenter cross-sectional study conducted in 27 referral obstetric units within the Brazilian Network for Surveillance of Severe Maternal Morbidity.Results A total of 82,388 women were surveilled: 9,555 women with severe maternal morbidity were included, and 942 (9.9%) of them had indirect causes of morbidity/mortality. There was an increased risk of higher severity among the indirect causes group, which presented 7.56 times increased risk of maternal death (prevalence ratio [PR]: 7.56; 95% confidence interval [95%CI]: 4.99–11.45). The main indirect causes of maternal death were H1N1 influenza, sepsis, cancer and cardiovascular disease. Non-public antenatal care (PR: 2.52; 95%CI: 1.70–3.74), diabetes (PR: 1.90; 95%CI: 1.24–2.90), neoplasia (PR: 1.98; 95%CI: 1.25–3.14), kidney diseases (PR: 1.99; 95%CI: 1.14–3.49), sickle cell anemia (PR: 2.50; 95%CI: 1.16–5.41) and drug addiction (PR: 1.98; 95%CI: 1.03–3.80) were independently associated with worse results in the indirect causes group. Some procedures for the management of severity were more common for the indirect causes group.Conclusion Indirect causes were present in less than 10% of the overall cases, but they represented over 40% of maternal deaths in the current study. Indirect causes of maternal morbidity/mortality were also responsible for an increased risk of higher severity, and they were associated with worse maternal and perinatal outcomes. In middle-income countries there is a mix of indirect causes of maternal morbidity/mortality that points to some advances in the scale of obstetric transition, but also reveals the fragility of health systems.
Keywords: maternal near-miss; maternal death; indirect causes; reproductive health